Defibrotide Prophylaxis of Sinusoidal Obstruction Syndrome in Adults Treated With Inotuzumab Ozogamicin Prior to Hematopoietic Stem Cell Transplantation - Giglio, Fabio; Xue, Elisabetta; Greco, Raffaella; Lazzari, Lorenzo; Clerici, Daniela Teresa; Lorentino, Francesca; Mastaglio, Sara; Marktel, Sarah; Lupo-Stanghellini, Maria Teresa; Marcatti, Magda; Corti, Consuelo; Bernardi, Massimo; et al. (Frontiers in Oncology, 2022)
Sinusoidal Obstruction Syndrome (SOS) is a life threatening HSCT complication and it rapidly evolves in Multiple Organ Dysfunction Syndrome, with a mortality exceding 80%. Precocity of defibrotide is the leading factor for efficacy. Its prophylactic use is recommended in the pediatric setting, but its value isn’t validated for adults, although factors for individual risk assessment are debated. We here present a real-world experience of Defibrotide prophylaxis in adults at very high risk of SOS. We treated with prophylactic Defibrotide and Ursodeoxycholic Acid seven patients receiving allogeneic HSCT for high risk B-ALL, previously treated with single agent Inotuzomab-Ozogamicin. They all had other high risk factors for SOS (previous hepatotoxicity, previous allo-HSCT, double alkylating conditioning). All patients received Treosulfan-Fludarabine conditioning, Thiotepa was added in 4 patients and 4GyTBI in 2 patients. GvHD prophylaxis included post-transplant cyclophosphamide, rapamycin and mycophenolate. Donor source was PBSC. Five patients received family MMRD transplant, 1 patient a MRD transplant and 1 patients a MUD transplant. Non-severe gastrointestinal bleeding occurred in two patients requiring defibrotide temporarily discontinuation. SOS occurred in 3/7 cases within 21 days and no late-onset SOS were diagnosed. SOS caused death in all cases. All three patients were characterized by a common pattern of very high risk factors by prior HSCT, they all received a myeloablative conditioning with Treosulfan-Thiotepa and a MMRD transplant. Defibrotide prophylaxis apparently failed to protect against the development of SOS in those patients treated with a double alkylator-based conditioning regimen, while a possible efficacy for the other high-risk patients is debatable.